DNA methylation pattern in pig in vivo produced embryos - Fulka, Josef; Fulka, Helena; Slavik, Tomas; Okada, Konosuke; Fulka, Josef (Histochemistry and cell biology, 2006)
DNA methylation/demethylation pattern, determined by 5-methylcytosine (5-MeC) immunostaining, was evaluated in porcine "in vivo" produced embryos from zygote up to the blastocyst stage. In one-cell stage embryos, only the maternal pronucleus showed a positive labeling whilst the paternal pronucleus showed almost no labeling. The intensity of labeling is high until the late morula stage. Blastocysts containing less than 100 cells showed the same intensity of labeling in both the inner cell mass (ICM) nuclei and the trophectodermal (TE) cell nuclei. Interestingly, with further cell multiplication, cells of the ICM became more intensively labeled when compared to TE cells. This distinct methylation pattern is even more profound in blastocysts containing about 200-300 cells and is not caused by the difference in the cell volume of ICM and TE cells.
Keywords: embryo savčí; Swine; zygota; Chromatin; Female; blastocysta; DNA Methylation; Animals; metylace DNA; Zygote; ženské pohlaví; Blastocyst; chromatin; zvířata; prasata; Embryo, Mammalian